PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR KOGNITIF FISIKA SISWA MAN PASIR PENGARAIAN - -, Zulman; Febriani, Yeza; Daruwati, Ika (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
The purpose of the research was to observe the effect of cooperative learning model of type Number HeadsTogether (NHT) influenced students physic cognitive learning result of MAN Pasir Pengaraian. This researchused the quantitative method. Using the saturated sampling technique, IX IPA 2 was elected as an experimentaland IX IPA 1 as a control class. Based on the result of analysis T-test, Tvalue=3,511 and Ttable= 2,01063. So, H1was accepted and H0 was refused. It can be concluded that cooperative learning models of type Number HeadTogether (NHT) influenced students physic cognitive learning result of MAN Pasir Pengaraian in the subjects ofworks and energy.